Traditional communities and integrative health policies - Lima da Silva, Denilma; Benício Novaz, Karoline; Maciel Dias, Samara; Cristine Moraes Coêlho, Thaynara; Emilia de Barros Santos, Suely; Bandeira de Moraes D’Angelo, Isabele (Seven Editora, 2023)
The health-disease process requires an integrative view of knowledge when working with traditional communities. The objective is to reflect on this process in traditional communities. Bibliographic research on the subject was carried out. As a result, we can say that indigenous, quilombola, and rural communities live surrounded by public policies dissociated from popular knowledge and way of life. Primary Health Care needs the training to serve these people.